The Role of Citizenship Education Teachers in Forming Quality Disciplined Student Character and Instilling the Value of Manners - Putri Amanda Sakinah Harahap (International Journal of Students Education, 2024)
This research aims to determine the role of citizenship education teachers in forming students' character of quality, discipline, and instilling the value of good manners. The research method used in this article is a systematic literature review. The author searches for journals that have been published on Google Scholar related to the title or topic research that the researcher has determined, the articles searched are limited to 10 articles, then the researcher filters them into 4 articles that are considered appropriate and related to the research topic. The results of the research show that as many as 4 articles from the search results can be seen about the role of citizenship education teachers in forming students' character of quality, discipline, and instilling the values of good manners. The results of the findings in the field and based on the results of observations show that so far the effort to shape students' disciplined character is by being a role model for students. This is done by teachers who must model good things for students in terms of dress, time discipline, not coming late, speaking politely, behaving and have good behavior and must obey the school rules, so not only do students obey the rules, teachers also have to obey them, enforcement of students in class and outside the classroom, for example, discipline students who are late and provide strict sanctions for those who violate school rules are carried out consistently and continuously and make it a habit.